2019
DOI: 10.1371/journal.pone.0217900
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behavior among individuals presenting with chronic cough at referral hospitals in Uganda; Missed opportunity for early tuberculosis diagnosis

Abstract: Background Tuberculosis (TB) is the 9 th leading cause of death from a single infectious agent. Patients live in a complex health care system with both formal and informal providers, and it is important that a TB diagnosis is not missed at the first interaction with the health care system. In this study, we highlight the health seeking behavior of patients and missed opportunities for early TB diagnosis for which interventions could be instituted to ensure early TB diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
(25 reference statements)
2
11
0
2
Order By: Relevance
“…It is of concern that many patients visited private health care facilities or pharmacies as their first point contact, incurring additional expenses in the process. Our findings corroborate studies in other settings where patients incurred higher costs and a circuitous path to care, [24] resulting in significant delays in accessing treatment [31]. The economic burden of TB treatment remains considerable, especially in poorer and developing countries without universal health coverage (UHC), including our study setting [5,32].…”
Section: Plos Onesupporting
confidence: 89%
“…It is of concern that many patients visited private health care facilities or pharmacies as their first point contact, incurring additional expenses in the process. Our findings corroborate studies in other settings where patients incurred higher costs and a circuitous path to care, [24] resulting in significant delays in accessing treatment [31]. The economic burden of TB treatment remains considerable, especially in poorer and developing countries without universal health coverage (UHC), including our study setting [5,32].…”
Section: Plos Onesupporting
confidence: 89%
“…9 The most common symptom found was cough which is very similar to other studies. 10 A statistically significant difference was found between PPTB and sociodemographic (gender, residence) as well as behavioural characteristics (tobacco use, alcohol use). There are no studies that have looked into the risk factors of PPTB, however, high use of tobacco among PPTB patients have been reported previously.…”
Section: Discussionmentioning
confidence: 93%
“…The assessment done in improving pathways to care through interventions co-created with communities in Malawi showed that clear pathways to care involve interventions that need to consider in contextual concerns by resolving personal level of socio-economic aspects and also boarder level of structural factors of gendered social dynamics and health system environment [20], the socio-economic and traditional factors are also substantial 'bottleneck' to hastening the uptake and utilisation of diagnostic and treatment tools for TB services [21], and adequate knowledge and positive health behaviour supports the TB patients in taking timely help from appropriate diagnosis and treatment health care outlets [22]. A quarter of the TB patients preferred for seeking care from the private health care service providers in Uganda [23]. However, more than seventy percent of people in Nepal still use and intend to visit the government health facilities to take TB diagnosis and treatment services.…”
Section: Discussionmentioning
confidence: 99%